Duality method in limit analysis problem of non-linear elasticity - Brigadnov, Igor A. (Computer Assisted Methods in Engineering and Science; Vol 10 No 4 (2003), 2023)
The limit analysis problem (LAP) for estimation of mechanical durability for non-linear elastic solids is examined. The appropriate dual problem is formulated. After the standard piecewise linear continuous finite-element approximation, the dual LAP is transformed into the problem of mathematical programming with linear limitations as equalities. This finite dimensional problem is solved by the standard method of gradient projection.